Where do we stand in cost of quality awareness? – Pakistan's case. (1st January 2014) - Qureshi, Sheheryar Mohsin; Majeed, Sadia; Khalid, Rameez
Quality management (QM) techniques have emerged as effective tools for organisations to satisfy their customers and achieve competitiveness. Cost of quality (COQ) is regarded as an important QM technique which measures the cost incurred in achieving better and improved product or service quality. This paper intends to contribute in the area of empirical study on quality costing by providing analysis of understanding and performance of the Pakistani industry (manufacturing and service sectors) in the context of practicing the basic principles of quality, QM and especially the effective implementation of COQ programme awareness. Findings of the study manifest that majority of the respondent firms have well implemented QM practices. Evidence also suggests that implementation of COQ programme helps enhance overall competitive position of the firm. However, due to lack of necessary understanding and relevant training on COQ, majority of the firms do not formally report COQ.